2022
DOI: 10.1186/s41256-022-00258-y
|View full text |Cite
|
Sign up to set email alerts
|

Does health economics research align with the disease burden in the Middle East and North Africa region? A systematic review of economic evaluation studies on public health interventions

Abstract: Introduction Economic evaluation studies demonstrate the value of money in health interventions and enhance the efficiency of the healthcare system. Therefore, this study reviews published economic evaluation studies of public health interventions from 26 Middle East and North Africa (MENA) countries and examines whether they addressed the region's major health problems. Methods PubMed and Scopus were utilized to search for relevant articles publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…Collectively, such identified mismatches support a very recent review of published economic evaluation studies of public health interventions from 26 MENA countries that found that the research output did not reflect current and upcoming disease burden and risk factors trends in the MENA region[ 27 ]. In the face of inevitable pressures from competing for alternative interventions, countries could direct their finite health budgets to meet the priority health needs of their populations to reach fair and efficient outcomes[ 55 ].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Collectively, such identified mismatches support a very recent review of published economic evaluation studies of public health interventions from 26 MENA countries that found that the research output did not reflect current and upcoming disease burden and risk factors trends in the MENA region[ 27 ]. In the face of inevitable pressures from competing for alternative interventions, countries could direct their finite health budgets to meet the priority health needs of their populations to reach fair and efficient outcomes[ 55 ].…”
Section: Discussionmentioning
confidence: 69%
“…In terms of trends and shortcomings, we noted that the number of publications on men’s SRHC were low, reflecting a generally low trend of research publications on other topics from the Arab world. For instance, a recent review of published economic evaluation studies from MENA observed very low output[ 27 ]; and similarly, pancreatic cancer and breast cancer bibliometric reviews also confirm the low contribution of Arab countries [ 28 , 29 ]. Whilst the precise reasons for such low output could be numerous, some authors proposed that it might reflect the regional instabilities and civil wars in MENA that impede medical research, increase brain drain, lead to isolation of research groups, and reallocate medical research funds towards other domains and to humanitarian relief [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The incidence of otitis media is high in South Asia, North Africa, and the Middle East, which is explained in part by the low socioeconomic status and poor healthcare services in these regions ( Zakaria et al 2020 ). Although the public health interventions in North Africa and the Middle East have improved, they are still at lower levels than those in other regions ( Nagi et al 2022 ). Nationally, the Republic of Korea had the largest increase in incidence of the disease.…”
Section: Discussionmentioning
confidence: 99%